Understanding the relationship between technological innovation and environmental sustainability under the silver lining of education - Iqbal, Kashif; Wang, Yichu; Danish,; Li, Nan; Khan, Salahuddin; Mahmood, Nasir; Shuo, Wang (Frontiers in Environmental Science, 2023)
Information and communication technology has gradually become one of the most important pillars of the economy. In addition to economic growth, environmental pollution is a product of information and communication technologies (ICTs) as well.However, whether and how ICTs may affect these systems is unclear. Based on a more comprehensive measurement of ICTs, the current study has investigated the impact of ICTs, education, and economic performance on environmental sustainability from 2000 to 2019 across 93 countries categorized as low-income, middle-income, and high-income.Contrary to preceding studies, this research has used advanced econometric techniques to counter heterogeneities and dependencies in the data and, thus, has produced more trustworthy and efficient results. The finding obtained from the Bias-corrected method of the moment's estimator and Driscoll and Kraal's standard error techniques are consistent.According to the results, ICTs have a heterogenous effect on environmental sustainability across low-, middle-and high-income countries. Further results have revealed that education plays a significant role in maintaining environmental sustainability across middle -and high-income groups but does not seem to do so for lower -income groups.Environmental education for all should be part of the policy measures to tackle climate change across all income groups.